Barriers and facilitators to implementing veterinary telemedicine in animal production - Guintard, Ana; Assié, Sébastien; Lefèvre, Lucile; Delsart, Maxime; Dile, Benoit; Millar, Nikky (Frontiers in Veterinary Science, 2024)
In France, in recent years, the field of veterinary medicine has witnessed a growing interest in veterinary telemedicine, driven by rapid technological advancements and a decline in the availability of veterinarians, particularly in remote and rural areas. However, there is a scarcity of literature addressing the barriers and facilitators of implementing telemedicine in veterinary practice. Therefore, this study aims to investigate the factors that influence the adoption of veterinary telemedicine for bovine, poultry and swine in France. Insights from both farmers and veterinarians were collected and subjected to qualitative analysis utilizing the COM-B model of behavior change. Significant barriers and facilitators were identified. Major hurdles encompass technological limitations, regulatory complexities, and concerns regarding the evolution of the veterinary profession. Conversely, the expertise of veterinarians, coupled with their understanding of their clients’ farms, and the potential for remote interventions, emerged as primary facilitators. The study emphasizes the critical role of regulation in ensuring ethical standards and maximizing the benefits of telemedicine. With clear regulatory frameworks in place, telemedicine holds promise for enhancing animal health and optimizing veterinary practice.